THEORIES OF PUBLIC POLICY FORMATION: A HISTORICAL OVERVIEW OF THE TOPIC (Journal of Teleological Science, 2023)
The existence of public policies is by no means a new theme in society. Even if the name is not recognized, it can be considered that the theme has been present since the earliest civilizations. The decisions taken to govern a population, however simple they may be, can be recognized as public policy. So much history associated with the theme also leads to a set of theories that seek to explain how this theme can be governed. With this article it will be possible, on a theoretical level, to group a whole set of theories and study them in a single article, and, on a practical level, to tell the reader a little more about the theme. To do this, a literature review is used. As conclusions it is understood that there are several theories that seek to explain the phenomenon of public policy formation, all with a set of specific characteristics that differ from other theories.
Keywords: Public Policy; Theories of Policy Formation; Public Administration